Exploring A Storage Concrete Rack Inspired By Sea Turtles - Tan Ying Shuang; Rawi, Firdaus (Research in Management of Technology and Business, 2023)
Researcher exploring a storage concrete rack inspired by sea turtles in this study as sea turtles is an endangered species and the population of sea turtles was in a serious decline. Meanwhile, public understanding and appreciation of wildlife is essential to its conservation. The objective of the research is to identify the criteria of the storage concrete rack inspired by sea turtles, to design the storage concrete rack inspired by sea turtles, and to develop a prototype of a storage concrete rack inspired by sea turtles. A questionnaire survey was conducted to 40 respondents that spent their time in a mall to collect the respondent opinion and determine the design criteria for the storage concrete rack. Progress work on this study continue with the visual research, sketches, final design and lastly mock-up process. The findings of the survey data showed the design criteria for a storage concrete rack is in concrete and wood/wood based material, in shape square/rectangular, in origin color of concrete, with 3 storage spaces and the main features considered by the respondent of the design is its functionality. The research on this study would become a reference to those who wants to deliver the awareness and environment education to the people and public.